Keeping the net up. - Comerford, R. (IEEE spectrum)
To most users, the Internet looks like another utility. Like a local phone or gas company, a local Internet service provider delivers the Net to their desktops. But that's not how it looks to the people who make the Net work. Although it must operate like a single entity, the Internet is made up of many independently owned and operated computers and networks. Keeping the parts working and keeping them working together are two separate tasks. To make any one of the Net's networks work, a new breed of company known as management service providers (MSPs) is now stepping in. Keeping the separate networks in step with one another is now the job of the two-year-old Internet Corporation for Assigned Names and Numbers (Icann), Marina del Rey, California. As things stand, the information highway looks bumpy for both. For their part, MSPs are still introducing themselves and their capabilities. At the same time, they are trying to figure out how to collaborate efficiently. As for Icann, it is under fire from start-up domain-name registrars and others who object to how it conducts business. It has till September 2001-a one year extension-to prove it can run the Internet in a way that is satisfactory to just about everyone